The Effects of Non-Compete Agreements on Different Types of Self-Employment: Evidence from Massachusetts and Utah - Ege Can; Frank M. Fossen (Institute of Labor Economics (IZA), 2020)
The economic effects of non-compete agreements have received increasing attention from academics and policymakers. This paper investigates how non-compete policies affect different types of self-employment. We exploit policy reforms in Utah and Massachusetts in 2016 and 2018, which decreased the enforceability of non-compete covenants, as quasi-experiments. We separate self-employment into self-employment with incorporated businesses (as a proxy for entrepreneurship) and self-employment with unincorporated businesses. Using representative individual-level data from the American Community Survey and the Current Population Survey, we estimate the probability of being self-employed with these different types of businesses, as well as entry into self-employment, and how these probabilities changed due to the reforms. Our findings show that the decrease in the enforceability of non-compete agreements in the two states resulted in a higher rate of incorporated self-employment in these states. In contrast, there was no sizable effect on the rate of unincorporated self-employment. Our results imply that states can promote entrepreneurial activity by reducing the enforceability of non-compete agreements.
Keywords: L26; O38; J23; 330; incorporated; non-compete agreements; entrepreneurship; unincorporated